Vamsapriya yadongensis sp. nov. (Vamsapriyaceae, Xylariales) from Southwestern China - Wang, Zhi-Yang; Thiyagaraja, Vinodhini; Maharachchikumbura, Sajeewa S. N.; Dissanayake, Lakmali S.; He, Shu-Cheng; Al-Otibi, Fatimah; Hyde, Kevin D; Zhao, Qi (Phytotaxa, 2024)
During an investigation of microfungi in the Xizang Autonomous Region (Tibet), China, a specimen was collected from unidentified terrestrial dead wood. Based on morphological and phylogenetic analyses, the specimen is described as a new species, Vamsapriya yadongensis. Phylogenetic analyses of combined ITS, LSU, rpb2, and tub2 sequence data indicate that Vamsapriya yadongensis is a sister to V. uniseptata. However, it differs from Vamsapriya uniseptata by its comparatively larger conidia, synnemata and higher number of conidial septa. Detailed morphological descriptions, illustrations, a synopsis table, phylogenetic affinities and key to the genus are provided.